PROSES PERJUANGAN SYEKH YUSUF DALAM MENYEBARKAN AGAMA ISLAM DI AFRIKA SELATAN (STUDI BIOGRAFI) - Faisal amir harahap; Isjoni Isjoni; Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Sheikh Yusuf is a scholar from Makasar who was born in Gowa, South Sulawesi July 13, 1627 under the name Muhammad Yusuf was given by Sultan Alaudin of the Gowa Kingdom itself. Muhammad Yusuf was taught religious sciences in Cikoang, and also wandering knowledge in various places including hajj at the age of 18 and temporarily settled in the Middle East to deepen the religion of Islam. The popularity of Joseph and his intellectual oceans is valued by many people as Sheikh Yusuf Al Makassari based on his origin, Makassar. Sometimes there is also add to give honorary title of Al Bantani (from Banten) which commonly used propagator and cleric. This study aims to determine: (1) to know the life history of Sheikh Yusuf while still in Indonesia. (2) To know how the process of traveling Sheikh Yusuf arrived in South Africa. (3) To know the struggle of Sheikh Yusuf in South Africa. This study uses the social sciences method, especially historical research methods, which can be used to approach the problem of the biography of Sheikh Yusuf in spreading Islam in Africa with data collection techniques to understand relevant books, archives, articles and documents. The results of this study show that (1) Sheikh Yusuf is a scholar from Indonesia precisely in Makassar (2) Sheikh Yusuf was thrown into Sri Lanka because he threatened the existence of the Dutch because he preached to the population about the danger of the Netherlands in Indonesia (3) Sheikh Yusuf in exile to Africa South because in Sri Lanka he preaches to the pilgrims because Sri Lanka is a haven for the pilgrims when leaving for pilgrimage to Mecca.Keywords: The Process of the Struggle of Sheikh Yusuf.